(untitled) (Fiep Bulletin - online, 2014)
This essay aims to reflect about the conditions of development opened by the new possibilities of free time by the proccess of automation; the human happiness as first goal of the Ethics in its classic conception; the mutual dependency between philosophy and happiness, education and health, also, the education of the wisdom as condition of quality of life, health and happiness.